Medicinske fund og det retslige udfald hos seksuelt misbrugte børn - Lene Aagaard Hansen; Svend Sabroe; Søren Johan Mikkelsen; Annie Vesterby Charles (Nordisk Tidsskrift for Kriminalvidenskab)
The association between the medical findings in cases regarding reported sexual abuse of children and the legal consequences of these cases has never been described in the Danish research literature. In total, 426 girls and 56 boys were examined at the request of the police at The Forensic Institute in Aarhus between 1996 and 2002. As many as 162 girls and 11 boys had positive anogenital findings and 165 perpetrators were convicted in court. There was no significant correlation between positive anogenital findings and legal outcome. The age of the child was significant.